The Effect of Business Capital Management on Business Success: The Role of Uncertainly Environment As a Moderation Variable for SDG 1 - Chrisna Suhendi; Luluk Muhimatul Ifada; Rita Rosalina (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The study examines the sustainability performance of Microfinance Institutions (MFIs) by analyzing the roles of competition, double bottom line performance, and digitalization in supporting the achievement of SDG 1, which focuses on poverty reduction. Specifically, this study investigates how financial sustainability and social outreach dimensions contribute to sustainable MFI development. Method: The study employs an unbalanced panel dataset obtained from the MIX Market database covering the period 1999–2019. The dataset consists of up to 20,120 institution-year observations from MFIs operating across various countries. Fixed-effects panel regression models are applied to examine the determinants of Operational Self-Sufficiency (OSS) as a measure of financial sustainability and Number of Active Borrowers (NAB) as an indicator of social outreach. The explanatory variables include profitability, loan portfolio, capital adequacy, funding structure, poverty outreach, total assets, competition, and digitalization. Results: The findings indicate that return on assets positively influences OSS, while loan volume significantly contributes to NAB. A higher deposit-to-loan ratio is associated with stronger financial sustainability. Furthermore, poverty outreach shows a positive relationship with OSS but a negative relationship with NAB. However, digitalization and its interaction with institutional size do not demonstrate statistically significant effects in the examined models. Novelty: To contribute to the microfinance literature by distinguishing financial sustainability and social outreach as separate dimensions of double bottom line performance and examining whether digitalization strengthens the relationship between institutional characteristics and sustainability outcomes. The findings provide insights into how MFIs can support SDG 1 through sustainable financial inclusion strategies.